Metodologi Fatwa K.H. Muhammad Syaf’i Hadzami - Muhammad Ardiansyah (Universitas Darussalam Gontor, 2017)
Fatwa is one of the heavy mandates on the shoulders of Moslem scholars. There are some conditions that must be fulflled before the fatwa could be used to solve the problems of the people. Basically, the fatwa replaces the task of the Prophet in conveying the shari’a law, then the scholars did not dare to be reckless in declaring any fatwa. Therefore, being a mufti is not only required by reading the translation of al-Qur’an or Hadith, or by searching on the google, or by copying broadcasts in social media. According to al-Shirazi, the intellectual condition that must be required to be a mufti is deep understanding toward al-Qur’an and Hadith, also understanding sources of speech such as ḥaqîqah-majâz, ‘âmm-khâṣṣ, Arabic language, nâsikh-mansûkh, ijmâ’, ikhtilaf, and tartîb al-adillah. While the moral requirements to be a mufti according to Imam Ahmad bin Hanbal are having pure intention, having broad knowledge, patience, and soul, having strong mentality to fulfl the task, having suffciency of life to avoid being inﬂuenced by others, and understanding the condition of society. This paper attempts to examine the fatwas of a mufti from Betawi who had lived in the modern era known as Mu’allim Syaf’i Hadzami. The fatwas were collected in a work entitled Tawḍîḥ al-Adillah. In this article, the author has concluded that Mu’allim uses eight complementary and relevant fatwa methodologies to solve today’s problems